Rock-Climbing Injuries in Yosemite National Park - Bowie, William S. (1988)
This study was presented in part at the annual meeting of the Wilderness Medical Society at Aspen, Colorado, in August 1986 and at “Mountain Medicine 1987,” Leavenworth, Washington, in November 1987. We questioned 220 injured rock climbers or their partners seen consecutively at the Yosemite (California) Medical Clinic over 3 ½ years regarding details of their accidents. Injury type and location were extracted from medical records and severity quantified. The National Park Service rescued 27% of the climbers. Injured climbers were characteristically male (88%) and experienced (mean 5.9 years) and typically fell while leading climbs (66%). Among 451 injuries, 50% were to the skin or subcutaneous tissues, while 28% involved the lower extremity and were predominantly fractures. In terms of each climber's most severe injury (n = 220), 45% involved the lower extremities (30% from the ankle alone). Head injury or hypothermia caused 12 of 13 fatalities, showing the lowest case-fatality rate reported to date among injured climbers (6%). Rescue personnel successfully managed airways in victims of head injuries, anticipated and treated complications of hypothermia, and stabilized fractures. Victims requiring immediate extensive surgical intervention or blood transfusion usually died before rescue could be effected.